Comparative study of colour Doppler vs. FNNAC findings in WHO grade II thyroid enlargement in adult females - M. S., Sudhakar Rao; T. P., Navneeth; C. J., John (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Thyroid gland disorders form one of the most common endocrinal and surgical problems encountered in clinical practice. FNNAC is widely accepted as the primary and better method than FNAC for investigation but has its disadvantages. Colour Doppler is a non-invasive, low cost, easily available and repeatable investigation with least patient discomfort and can be valuable in detection of benign and malignant thyroid enlargements. Methods: Forty cases of adult females with WHO grade 2 thyroid enlargement attending the department of otorhinolaryngology selected on simple random basis were included in this study. Following written consent, Colour Doppler scanning and FNNAC test were done on the thyroid swelling and the results were analysed. Results: The mean age of patients was 32.44 years. The mean age of malignancy was 44.66 years and showed statistically significant association. The Resistive and Pulsatility index and combination of both were found to have statistically significant results in detecting malignant and benign lesions The sensitivity, specificity, positive and negative predictive values of RI and PI were 83.33%, 94.12%, 71.43%, 96.97% and 50%, 94.12%, 60% and 91.43% respectively. On combining both the indices, the sensitivity was 91.67% and the positive predictive value was 97.06%. Conclusions: Colour Doppler can differentiate between benign and malignant thyroid enlargements using Resistive index (of>0.75) and Pulsatility Index (of>1.5) and can be a complementary diagnostic tool in the thyroid enlargement lesions, considering its accuracy, cost-effectiveness, easy availability and non-invasive repeatable nature.